The Interpretation of Judge Shurayh through the Book "Akhbar al-Qudat" by Waki’ (Compilation and Study) - الحصيني د.أحمد (Thi Qar Arts Journal, 2024)
This research included a study of Judge Shurayh’s interpretative statements, as mentioned in the book "Akhbar al-Qudat" by Waki’. It aimed to highlight the topics of Quranic sciences related to them and compare Judge Shurayh’s interpretation with others, noting points of agreement and disagreement. The consistent methodology for writing this research was the inductive-analytical method. Its main results were: 1. The topics of Quranic sciences included in Judge Shurayh’s interpretation through this research were: the strange words of the Holy Quran, the ambiguous verses of the Quran, and the direction of readings. 2. Judge Shurayh’s interpretation agreed with the consensus of interpreters in one instance, agreed with the most likely opinions of interpreters in two instances, and disagreed with the most likely opinion in two instances. The researcher recommends studying Judge Shurayh’s interpretation and comprehending it in a well-edited academic thesis.